Hsp70's RNA-binding and mRNA-stabilizing activities are independent of its protein chaperone functions - Kishor, Aparna (J Biol Chem, 2017)
Hsp70 is a protein chaperone that prevents protein aggregation and aids protein folding by binding to hydrophobic peptide domains through a reversible mechanism directed by an ATPase cycle. However, Hsp70 also binds U-rich RNA including some AU-rich elements (AREs) that regulate the decay kinetics of select mRNAs and has recently been shown to bind and stabilize some ARE-containing transcripts in cells. Previous studies indicated that both the ATP- and peptide-binding domains of Hsp70 contributed to the stability of Hsp70–RNA complexes and that ATP might inhibit RNA recruitment. This suggested the possibility that RNA binding by Hsp70 might mimic features of its peptide-directed chaperone activities. Here, using purified, cofactor-free preparations of recombinant human Hsp70 and quantitative biochemical approaches, we found that high-affinity RNA binding requires at least 30 nucleotides of RNA sequence but is independent of Hsp70's nucleotide-bound status, ATPase activity, or peptide-binding roles. Furthermore, although both the ATP- and peptide-binding domains of Hsp70 could form complexes with an ARE sequence from VEGFA mRNA in vitro, only the peptide-binding domain could recover cellular VEGFA mRNA in ribonucleoprotein immunoprecipitations. Finally, Hsp70-directed stabilization of VEGFA mRNA in cells was mediated exclusively by the protein's peptide-binding domain. Together, these findings indicate that the RNA-binding and mRNA-stabilizing functions of Hsp70 are independent of its protein chaperone cycle but also provide potential mechanical explanations for several well-established and recently discovered cytoprotective and RNA-based Hsp70 functions.